Cerebrospinal fluid tumor DNA for liquid biopsy in glioma patients' management: Close to the clinic?. (February 2020) - Simonelli, Matteo; Dipasquale, Angelo; Orzan, Francesca; Lorenzi, Elena; Persico, Pasquale; Navarria, Pierina; Pessina, Federico; Nibali, Marco Conti; Bello, Lorenzo; Santoro, Armando; Boccaccio, Carla
Highlights: Liquid biopsy of circulating tumor DNA (ct-DNA) represents a promising tool for genetic diagnosis of gliomas. The best source of ct-DNA in glioma patients is the cerebrospinal fluid (CSF) from surgical procedures or lumbar puncture. Proximity of glioma to intracerebral cavities or brain surface is a key factor for ct-DNA release in CSF. CSF ct-DNA detection and molecular analysis could be performed with PCR-based methods or NGS-based techniques. CSF ct-DNA liquid biopsy would greatly assist every step of gliomas management: from diagnosis to tumor response monitoring. Abstract: Cell-free circulating tumor DNA (ct-DNA) reflecting the whole tumor spatial and temporal heterogeneity currently represents the most promising candidate for liquid biopsy strategy in glioma. Unlike other solid tumors, it is now widely accepted that the best source of ct-DNA for glioma patients is the cerebrospinal fluid, since blood levels are usually low and detectable only in few cases. A cerebrospinal fluid ct-DNA liquid biopsy approach may virtually support all the stages of glioma management, from facilitating molecular diagnosis when surgery is not feasible, to monitoring tumor response, identifying early recurrence, tracking longitudinal genomic evolution, providing a new molecular characterization at recurrence and allowing patient selection for targeted therapies. This review traces the history of ct-DNA liquid biopsy in the field of diffuse malignant gliomas, describes its current status and analyzes what are the future perspectives and pitfalls of this potentially revolutionary molecular tool.